How are the requirements enabling efficient economic and financial in government contracting processes? (2015)
through this letter, to develop a study about the evolutionary process of the qualifying requirements in economic matters - financial, within the state contracting processes in Colombia. Given the fact that the theme to be developed is a purely legal framework is necessary to return to the historical context of the Contracting State to meet the economic requirements as born - Financial and what is its purpose.